Epidemiological and clinical features of nail disorders in patients presenting to a pediatric dermatology outpatient clinic - Ayşegül Yalçinkaya İyidal; Funda Erduran; Yildiz Hayran; Güneş Gür Aksoy; Halil İbrahim Yakut; Akin Aktaş (Medicine, 2026)
Nail disorders in the pediatric population encompass a broad spectrum of conditions with distinct epidemiological and clinical profiles compared with those observed in adults. Despite their clinical relevance, comprehensive data on the prevalence, distribution, and associated factors of pediatric nail disorders remain scarce. This study was designed to test the hypothesis that the prevalence and etiological distribution of nail disorders vary significantly across pediatric age groups and are associated with identifiable clinical and demographic factors. This cross-sectional observational study enrolled 1530 consecutive patients aged 0 to 17 years presenting to a tertiary pediatric dermatology outpatient clinic between July 2022 and July 2023, regardless of the primary reason for visit. Patients were stratified into 4 age groups: 0 to 2, 3 to 5, 6 to 11, and 12 to 17 years. The primary objective was to estimate the prevalence and clinical distribution of nail disorders stratified by age and mode-of-detection; the secondary objective was to characterize associated demographic and clinical factors. Nail abnormalities were identified in 16.93% (95% confidence interval [CI], 15.10–18.91) of patients, of whom 71.8% were newly identified during consultations undertaken for non-nail concerns; only 4.8% had presented with a nail-related primary complaint. A total of 26 distinct nail disorders were documented: punctate leukonychia (3.6%), periungual verruca (3.1%), and onychomadesis (1.8%) were most prevalent. The distribution of nail disorders varied substantially across age groups with prevalence increasing monotonically from 9.4% in the 0 to 2-year group to 25.4% in the 12 to 17-year group ( P < .001): congenital malalignment of the great toe predominated in the 0 to 2-year group, onychomadesis in the 3 to 5-year group, and punctate leukonychia in both the 6 to 11- and 12 to 17-year groups. Systematic dermoscopic documentation, available for 138 affected patients (53.3%), revealed disorder-specific features supporting differential diagnosis. Pediatric nail disorders were more prevalent than symptom-driven consultations alone would suggest, with a markedly age-dependent variation in both type and distribution, consistent with the prespecified hypothesis. As findings derive from a tertiary referral population, generalizability to the broader pediatric community cannot be assumed. These observations are hypothesis-generating and specific to tertiary referral settings; whether systematic nail examination during routine assessment improves early recognition in the broader pediatric population requires confirmation in community-based studies.